Legal Aspects of the Conservation and Protection of Biodiversity – Example of Lake Palić - Batanjski, Vera; Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Lake and wetland ecosystems are kept significant, unique biodiversity. An example of this is Lake Palić – Regional Nature Park, IBA and IPA area. It is under various negative pressures created by human communities. The work that we show is the research result of a fragment of reality. The aim is to document, in a practical way, the claim obliged to form our practical thinking and increase efforts of practical action on further approach to the issue in full compliance with the regulation, that the knowledge of biology and ecology was and still is a prerequisite for the formation and implementation. This clearly means a multidisciplinary approach by biologist and lawyer authors to the problems of the whole Lake Ludaš (the "Ramsar point") – Palić ecological entity, which, as such, is protected by a complex set of international and national legislations, unfortunately, is injured in practice.